Can staff and patient perspectives on hospital safety predict harm-free care? An analysis of staff and patient survey data and routinely collected outcomes. Issue 6 (10th April 2015) - Lawton, Rebecca; O'Hara, Jane Kathryn; Sheard, Laura; Reynolds, Caroline; Cocks, Kim; Armitage, Gerry; Wright, John
Abstract : Background: Patients have the potential to provide feedback on the safety of their care. Recently, tools have been developed that ask patients to provide feedback on those factors that are known to contribute to safety, therefore providing information that can be used proactively to manage safety in hospitals. The aim of this study was to investigate whether the safety information provided by patients is different from that provided by staff and whether it is related to safety outcomes. Method: Data were collected from 33 hospital wards across 3 acute hospital Trusts in the UK. Staff on these wards were asked to complete the four outcome measures of the Hospital Survey of Patient Safety Culture, while patients were asked to complete the Patient Measure of Safety and the friends and family test. We also collated publicly reported safety outcome data for 'harm-free care' on each ward. This patient safety thermometer measure is used in the UK NHS to record the percentage of patients on a single day of each month on every ward who have received harm-free care (ie, no pressure ulcers, falls, urinary tract infections and hospital acquired new venous thromboembolisms). These data were used to address questions about the relationship between measures and the extent to which patient and staff perceptions of safety predict safety outcomes. Results: The friends and family test, a single item measure of patient experience was associated with patients' perceptions of safety, but was not associated with safety outcomes. Staff responses to the patient safety culture survey were not significantly correlated with patient responses to the patient measure of safety, but both independently predicted safety outcomes. The regression models showed that staff perceptions (adjusted r 2 =0.39) and patient perceptions (adjusted r 2 =0.30) of safety independently predicted safety outcomes. When entered together both measures accounted for 49% of the variance in safety outcomes (adjusted r 2 =0.49), suggesting that there is overlap but some unique variance is also explained by these two measures. Based on responses to the Patient Measure of Safety it was also possible to identify differences between the acute Hospital Trusts. Discussion: The findings suggest that although the views of patients and staff predict some overlapping variance in patient safety outcomes, both also offer a unique perspective on patient safety, contributing independently to the prediction of safety outcomes. These findings suggest that feedback from patients about the safety of the care that they receive can be used, in addition to data from staff to drive safety improvements in healthcare. Trial registration number: ISRCTN07689702.